(untitled) (Global Journal of Medical Research, 2020)
Dracaena deisteliana and Sporobolus indicus are medicinal plants with broad use in Cameroonian folk medicine to treat several infectious diseases. This study aimed to investigate the phytochemical composition, the antimicrobial and antiradical properties of methanol extracts of the leaves, stem and whole plant of D. deisteliana, and S. indicus. The phytochemical test was undertaken using standard methods. Agar well diffusion was used for sensitivity test while the microdilution method was used to determine the minimum inhibition concentrations (MICs) and the minimum bactericidal/fungicidal concentrations (MBCs/MFCs). The antiradical property of the plant extracts was performed using the 2.2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay.